Development and Validation of the Chinese Modesty Scale (CMS) - Xiong, Mimi; Wang, Fengyan; Cai, Ruixue (Frontiers in Psychology, 2018)
This paper describes the development and method of validation of the Chinese Modesty Scale (CMS). Based on Wang’s dualistic model for value and instrumental modesty, our study employed a review of the literature, in-depth interviews, open-ended investigations and feedback from experts. An initial 14-item scale for analyzing the issue of “Chinese modesty” was developed. Then we explored the dimensions and final items of this CMS using item analysis and exploratory factor analysis (EFA) with sample 1 (n = 406). After that, we conducted a confirmatory factor analysis (CFA) to replicate the factor structure obtained through EFA with a refined, independent, 12-item scale (n = 662). Results confirmed the dualistic model (for value and instrumental modesty) on which this scale was based. That is, we found that there are two kinds of “Chinese modesty”: value modesty and instrumental modesty. As a valid, reliable scale, the Chinese modesty scale can therefore be used to measure the “Chinese modesty” of/in different age groups.